Growth and genetic parameters of progenies of Cordia trichotoma in the juvenile phase - Almeida, Rodolfo Soares de; Assis, Guilherme da Silva; Melo, Lucas Amaral de; Silva, Gabriel Campos Almeida; Resende, Eduardo Willian Andrade; Luz, Matheus Santos; Resende, João Cortes Regadas (Scientia Agraria Paranaensis, 2021)
Increasing the productive potential of native species is a challenge for forest genetic improvement. Progeny tests are efficient tools to determine the reproductive capacity of individuals and to assist with the selection of superior genotypes. Cordia trichotoma (Vell.) Arrab. ex Steud, is a native species of commercial interest due to its high potential for sawn wood. The performance of seedling production from different progenies was the objective of this work. Seeds were collected from 34 matrices selected phenotypically and georeferenced in the region of Lavras - MG. The experiment was conducted in a completely randomized design with 4 replications of 12 plants. Germination after 70 days of sowing, survival and height at 170 days after germination were evaluated. Height and genetic parameters were estimated according to mixed REML / BLUP models using the Selegen software model 82. Progeny 104 (70.8%) was superior in germination and progenies 86 (35.42%), 92 (35.42%) and 111 (43.75%) had the highest survival rates. Height shows high values for the individual additive genetic variation coefficient (49.18%) and genotypic variation coefficient between progenies (24.59%) and moderate values of heritability in the restricted individual sense (0.45) and heritability within progenies (0.38). Due to high values for the coefficient of genotypic variation and moderate values of heritability, there is a potential for height improvements. Progenies 104 stand out in the germination and the progenies 86, 92 and 111 in the seedlings survival). Regarding height, progeny 95 is the only one that stands out negatively.